Randomizing the Unfolded State of Peptides (and Proteins) by Nearest Neighbor Interactions between Unlike Residues. Issue 13 (26th February 2015) - Toal, Siobhan E.; Kubatova, Nina; Richter, Christian; Linhard, Verena; Schwalbe, Harald; Schweitzer‐Stenner, Reinhard
Abstract To explore the influence of nearest neighbors on conformational biases in unfolded peptides, we combined vibrational and 2D NMR spectroscopy to obtain the conformational distributions of selected "GxyG" host–guest peptides in aqueous solution: GDyG, GSyG, GxLG, GxVG, where x/y=A, K, L, V. Large changes of conformational propensities were observed due to nearest‐neighbor interactions, at variance with the isolated pair hypothesis. We found that protonated aspartic acid and serine lose their above‐the‐average preference for turn‐like structures in favor of polyproline II (pPII) populations in the presence of neighbors with bulky side chains. Such residues also decrease the above‐the‐average pPII preference of alanine. These observations suggest that the underlying mechanism involves a disruption of the hydration shell. Thermodynamic analysis of 3J(HN, Hα) (T) data for each x, y residue reveals that modest changes in the conformational ensemble masks larger changes of enthalpy and entropy governing the pPII↔β equilibrium indicating a significant residue dependent temperature dependence of the peptides' conformational ensembles. These results suggest that nearest‐neighbor interactions between unlike residues act as conformational randomizers close to the enthalpy–entropy compensation temperature, eliminating intrinsic biases in favor of largely balanced pPII/β dominated ensembles at physiological temperatures.